PENGEMBANGAN MEDIA PUZZLE PETA TEMA ORGAN GERAK HEWAN DAN MANUSIA MATERI KONDISI GEOGRAFIS INDONESIA KELAS V SD - Rizky, Nora; Fuadiah, Nyiayu Fahriza; Murjainah, Murjainah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research was motivated by the low understanding of students in understanding learning materials for class VA SD Negeri 12 Muara Pinang it can be seen from the results of interviews with class VA teachers. The lack of learning media that is taught during the learning process causes students' low understanding in understanding learning materials. This study aims to produce a media puzzle map material for the geographical conditions of Indonesia that is valid, practical, and effective. The research method used in the 4D development model consists of four stages, namely define, design, develop, and disseminate. Data analysis techniques were carried out using validity, practicality, andeffectiveness. The results of the study using the average percentage showed the results of the media validation questionnaire analysis obtained a percentage of 97.5% with very valid criteria and material validation obtained a percentage of 93.75% with very valid criteria then the results of the one-to-one questionnaire analysis obtained 93.33% with very practical criteria, a small group got 93.49% with very practical criteria. Furthermore, the level of effectiveness of the map puzzle media at the pretest was 50.25% and the post-test was 84.6%, an increase of 34.35% from 20 students. The difference between the pretest and post-test values can be obtained that N-Gain 0.71 is included in the high category. The results can be concluded that this map puzzle media is valid for use in thematic learning. It is hoped that the results of this study can be used as material for further research to be able to develop a puzzle media for material maps of different geographical conditions in Indonesia.